1985
DOI: 10.1042/bj2290387
|View full text |Cite
|
Sign up to set email alerts
|

Protection of rats by clofibrate against the hypoglycaemic and toxic effects of hypoglycin and pent-4-enoate. An ultrastructural and biochemical study

Abstract: An ultrastructural and biochemical study of the toxic and hypoglycaemic effects of hypoglycin and pent-4-enoate was made on the livers of normal and clofibrate-fed rats. Injection of hypoglycin to rats doubles (from 22% to 44%) the volume fraction of mitochondria and decreases (from 1.05% to 0.26%) the volume fraction of peroxisomes in hepatocytes. The fast-acting toxin pent-4-enoate causes few ultrastructural changes except for the accumulation of lipids. In male adult rats fed with 0.5% clofibrate in their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…In the fraction that, based on the catalase measurement, was mostly enriched in peroxisomes, TPP increased to 177 ± 2 pmol/mg protein (mean ± SEM of three experiments), about twofold more in comparison with the L-fraction (79.4 ± 11 pmol/mg protein). Assuming that the peroxisomal compartment accounts for 2–2.5% of the total hepatic protein content [11,12] and occupies approximately 10 μl per ml of liver [13,14], one can estimate the intraperoxisomal TPP concentration at approximately 65–85 μM. As part of the TPP may leak out of peroxisomes during the fractionation procedure, this value represents a minimal estimation, but appears to be higher than the cytosolic concentration, estimated at 15–20 μM assuming that the cytosol accounts for 80% of the hepatocyte volume [13].…”
Section: Resultsmentioning
confidence: 99%
“…In the fraction that, based on the catalase measurement, was mostly enriched in peroxisomes, TPP increased to 177 ± 2 pmol/mg protein (mean ± SEM of three experiments), about twofold more in comparison with the L-fraction (79.4 ± 11 pmol/mg protein). Assuming that the peroxisomal compartment accounts for 2–2.5% of the total hepatic protein content [11,12] and occupies approximately 10 μl per ml of liver [13,14], one can estimate the intraperoxisomal TPP concentration at approximately 65–85 μM. As part of the TPP may leak out of peroxisomes during the fractionation procedure, this value represents a minimal estimation, but appears to be higher than the cytosolic concentration, estimated at 15–20 μM assuming that the cytosol accounts for 80% of the hepatocyte volume [13].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of feeding with clofibrate on rat liver are complex, including a 6-10-fold increase in peroxisomal f-oxidation, a 2-3-fold increase in mitochondrial fl-oxidation, a 2-fold increase in the fatty-acid-binding Z-protein (Renaud et al, 1978) and a 3-fold increase in total contents of CoASH and carnitine (Mannaerts et al, 1978). Van Hoof et al (1985) showed that the virtually complete inactivation of butyryl-CoA dehydrogenase activity caused by administration of hypoglycin in untreated rats was partly prevented by Vol. 246 pretreatment with clofibrate.…”
Section: Discussionmentioning
confidence: 99%
“…The significant organic aciduria in clofibrate-fed rats given hypoglycin indicates that the metabolic disturbances were only partly prevented, but, in this mode, those remaining were not enough to cause hypoglycaemia, hypothermia or death (see Van Hoof et al, 1985). This protection may be due to both a decrease in the extent of the inhibitions after administration of hypoglycin and an increased resistance to these inhibitions by clofibrate.…”
Section: Discussionmentioning
confidence: 99%
“…Selective accumulation of one or several intermediates of phytanic acid catabolism in infantile Refsum's disease cannot be definitely ruled out. As in the case of hypoglycin (25), such metabolites might be toxic for peroxisomes. Overload of the entire set of reactions leading to phytanic acid breakdown has been achieved by exogenous administration of high doses of phytol to mice.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrastructural and biological findings reported in infantile Refsum's disease have not yet been examined in adult-onset Refsum's disease; peroxisomes were studied in cultured fibroblasts from adult-onset Refsum patients, but not in other cell types (24). It was recently demonstrated that certain metabolites (hypoglycin) can have a destructive effect on rat liver peroxisomes (25). We now investigate the effect of phytanic acid accumulation following enhanced dietary supply of phytol on peroxisomal abundance and enzymology in several organs from mice.…”
mentioning
confidence: 99%